Giant velum interpositum meningioma in a child - Aliasgar V Moiyadi; Prakash Shetty (Indian Journal of Medical and Paediatric Oncology)
Intraventricular meningiomas are rare, but are relatively more often seen in children. Large size at presentation often obscures anatomical details. A particular subset of such tumors arising from the velum interpositum pose a significant surgical challenge. Thorough preoperative imaging, especially with respect to the course of the deep venous structures, provides useful evidence as to the origin. Preservation of venous anatomy at surgery is vital. We describe a 3-year-old girl with a giant velum interpositum meningioma that was completely excised with excellent outcome. This is probably the youngest such case reported.